Ponto de Partida: A political theater in the military dictatorship (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this interview, the actor Antonio Petrin (1938) comments his participation in the cast of the first staging of the play Ponto de Partida (1976), an important Brazilian musical, written by Gianfrancesco Guarnieri (1934-2006) and directed by Fernando Peixoto (1937-2012). It is a play that sought to allude to the death of journalist Vladimir Herzog (1937-1975), tortured and murdered by the State during the military dictatorship in Brazil (1964-1985). In May 2021, given the health crisis caused by the new coronavirus (COVID-19), the interview was conducted through a video call.
Keywords: Brazilian theater; Military dictatorship; Vladimir Herzog; Antonio Petrin